Pestalotia versicolor a Predominant Pathogen Associated with Decline Disease of Mango in Sub-tropical Zone of Himachal Pradesh - Jarial, Kumud; Jarial, R. S.; Thakur, P. D.; Banyal, Sanjeev K.; Mandradia, R. K. (International Journal of Bio-resource and Stress Management, 2023)
During a survey conducted in mango growing areas of four districts viz., Hamirpur, Bilaspur, Una and Kangra of Himachal Pradesh in 2013–14, the severity of mango decline ranged between 25.73% at Bairi Rajdiyan (Bilaspur) to 64.68% at Mataur (Kangra) while, its incidence ranged between 50.0% at Salauni (Hamirpur) and Nagrota Bagwan (Kangra) to 100% at various locations in all the four districts. Main symptoms observed included die back, gummosis and bark splitting. Diseased samples exhibiting different symptoms were collected and brought to laboratory for isolation and purification. Pathogenicity of the isolates was tested on young mango seedlings and pathogen isolates exhibiting similar cultural characters and sporulation were designated as I1, I2, I3 andI4, which were later identified respectively as Phomopsis mangiferae, Pestalotia versicolor, P. versicolor and Colletotrichum gloeosporoides under ITCC identification numbers 9457.14, 9458.14, 9459.14 and 9460.14. P. versicolor (I2 and I3)associated with die back, gummosis and bark splitting was observed to be prevalent in almost all the 22 locations surveyed while, P. mangiferae and C. gloeosporoides were prevalent in only 2 and 5 locations, respectively. During in vitro assay of fungicides, complete inhibition of P. mangiferae and P. versicolor was recorded with carbendazim as well as mancozeb and carbendazim as well as hexaconazole, respectively at all concentrations while C. gloeosporoides was inhibited completely by hexaconazole tested at 2000 ppm. P. versicolor was the predominant pathogen associated with die back, gummosis and bark splitting symptoms of decline complex and constitutes the new record from Himachal Pradesh.